Evaluasi Kinerja Crushing Plant Batu Andesit PT Widaka Indonesia di Kelurahan Jelekong, Kecamatan Baleendah, Kabupaten Bandung, Provinsi Jawa Barat - Tubagus Hidayatullah; Sriyanti; Zaenal (Bandung Conference Series: Mining Engineering, 2022)
Abstract. This research is to determine the crushing process of andesite stone, to find out what obstacles occur before and after replacing the jaw plate and setting the tool, to get the efficiency value used for evaluating the performance of the crushing plant. The tools used are jaw crusher, secondary crusher, 2 vibrating screens and 12 conveyor belts. The results of this study are the results of the calculated resistance data obtained a value in the form of work efficiency of 75.73% with an effective time of 5.68 hours/day in condition A. In condition B, the effective time was 6.23 hours/day with an effectiveness of 83.06%. For the unit crushing plant, the effectiveness of the jaw crusher increases. Mechanical Availability increased by 3.65%, Physical Availability value increased by 2.41%, Effective of Utilization value increased by 15.75%, and Effectiveness of Utilization value increased by 13.04%. For cone crusher 1 also increased, the MA value was 13.10%, the PA value was 8.57%, the EU value was 23.79%, and the UA value was 14.02%. For cone crusher 2 there is a decrease in the MA value by 3.11% and the PA value by 3.26%, while the EU value increases by 6.62%, and the UA value increases by 10.21%. The resulting production is jaw crusher of 90,476 tons/hour in condition A while in condition B of 125.479 tons/hour, cone crusher 1 of 105.030 tons/hour, and cone crusher 2 of 100.575 tons/hour, with looses of 2,082 tons/day . The production target is 770 Tons/day, the average actual production in condition B is 384.89 tons/day and in condition B 524.52 tons/day, the production target in condition A and condition B is not achieved. Abstrak. Penelitian ini untuk mengetahui proses peremukan batu andesit, mengetahui apa saja hambatan yang terjadi sebelum dan sesudah penggantian jaw plate dan setting alat, untuk mendapatkan nilai efisiensi yang digunakan untuk evaluasi kinerja dari crushing plant. Alat yang digunakan yaitu jaw crusher, secondary crusher, vibrating screen 2 buah, dan belt conveyor sebanyak 12 buah. Hasil dari penelitian ini yaitu data hambatan yang dihitung didapatkan nilai berupa efisiensi kerja sebesar 75,73% dengan waktu efektif sebesar 5,68 jam/hari pada kondisi A. Pada kondisi B mendapat waktu efektif 6,23 jam/hari dengan efektivitas 83,06%. Untuk unit crushing plant, efektivitas jaw crusher naik. Pada Mechanical Availability naik sebesar 3,65%, nilai Phisycal Availability naik sebesar 2,41%, nilai Efective of Utilization naik sebesar 15,75%, dan nilai Efective of Utilization naik sebesar 13,04%. Untuk cone crusher 1 juga mengalami kenaikan, nilai MA sebesar 13,10%, nilai PA sebesar 8,57%, nilai EU sebesar 23,79%, dan nilai UA Sebesar 14,02%. Untuk cone crusher 2 terdapat penurunan nilai MA sebesar 3,11% dan nilai PA sebesar 3,26%, sedangkan nilai EU naik sebesar 6,62%, dan nilai UA naik sebesar 10,21%. Produksi yang dihasilkan yaitu jaw crusher sebesar 90,476 Ton/jam pada kondisi A sedangkan pada kondisi B sebesar 125,479 Ton/jam, cone crusher 1 sebesar 105,030 ton/jam, dan cone crusher 2 sebesar 100,575 ton/jam, dengan looses sebesar 2,082 ton/hari. Target produksi sebesar 770Ton/hari, produksi aktual rata-rata pada kondisi B yaitu 384,89 Ton/hari dan pada kondisi B 524,52 ton/hari maka target produksi pada kondisi A dan kondisi B tidak tercapai.